Nepenthes ridzaiana and n. × langkawiensis (Nepenthaceae), a new species and a new nothospecies of pitcher plants from Langkawi Island, Malaysia - Latif, A.; Mohd Norfaizal, G.; Besi, E.E.; Mat-Esa, M.E.; Go, R.; Sandin, D.; Endot, Mohd. Ridzuwan; Norulhuda Ali,, C; Khairuddin Perdan, Norulhuda Ali,; Yapp, E.J.; Mohd Nor Firdaus, R. (Malaysian Forester, 2024)
A new species and a new nothospecies of Nepenthes, N. ridzaiana Latiff, M.N. Faizal et Besi, sp. nov. and Nepenthes × langkawiensis Latiff, M.N. Faizal et Besi nothosp. nov. are herein described and illustrated from Langkawi Island, Kedah, Malaysia. These taxa are so far known only from a few populations in hilly and lowland forest areas of Langkawi Island. An updated identification key to the Nepenthes of Peninsular Malaysia is also provided.